Trust and Mistrust - Common and Specific Psychological Characteristics - A B Kupreychenko (Peoples' Friendship University of Russia (RUDN University), 2008)
The article considers the problem of studying trust and mistrust as relatively independent phenomena, which is rather a new point of view in psychology.